Histochemical Studies on Hemal Nodes of Indian Buffalo - Kaur, Jaideep (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on hemal nodes of buffalo (n=12) of two different age groups to study the distribution of various histochemical moieties. The capsule of the hemal node showed mixed reaction for mucopolysaccharides. The lymphocytes and lymphoid follicles, except in the area of germinal centre showed higher content of acid mucopolysaccharides as compared to calves. Erythrocytes were devoid of acid mucopolysaccharides content in both the groups. Neutral mucopolysaccharides content was higher in capsule, trabeculae and erythrocytes whereas variable reaction was observed in lymphoid follicles indicating differential maturity. Fine Sudanophilic lipid droplets were observed in capsule of hemal node. The capsule, trabeculae, lymphoid follicles, sinuses and erythrocytes showed moderate to strong activity for proteins. The distribution of various histochemical moieties and presence of variable activity of different enzymes in hemal nodes was correlated with maturation of lymphocytes and development of different metabolic pathways.